A Comparison of Dysautonomias Comorbid with Cyclic Vomiting Syndrome and with Migraine. (6th December 2009) - Chelimsky, Gisela; Madan, Shruti; Alshekhlee, Amer; Heller, Elizabeth; McNeeley, Kevin; Chelimsky, Thomas
Abstract : Cyclic vomiting syndrome (CVS) shares many features with migraine headache, including auras, photophobia, and antimigrainous treatment response being traditionally viewed as a migraine variant. Aims . To determine whether CVS is associated with the same disorders as migraine headache, and compare these associations to those in healthy control subjects. Methods . Cross-sectional study of patients utilizing the ODYSA instrument, evaluating the probability of 12 functional/autonomic diagnoses, CVS, migraine, orthostatic intolerance (OI), reflex syncope, interstitial cystitis, Raynaud's syndrome, complex regional pain syndrome (CRPS), irritable bowel syndrome, functional dyspepsia, functional abdominal pain, fibromyalgia, and chronic fatigue syndrome. Control subjects were age-matched gender-matched friends. Patients had to fulfill criteria for CVS or migraine, while control subjects could not. Results . 103 subjects were studied, 21 with CVS, 46 with migraine and 36 healthy controls. CVS and migraine did not differ in the relative frequencies of fibromyalgia, OI, syncope, and functional dyspepsia. However, CVS patients did demonstrate a significantly elevated frequency of CRPS. Conclusions . Although CVS and migraine clearly share many of the same comorbidities, they do differ in one important association, suggesting that they may not be identical in pathophysiology. Since OI is common in CVS, treatment strategies could also target this abnormality.